Global transformations, local choices Navigating the impacts of Artificial Intelligence on education - Hillman, Velislava; Esquivel, Molly; Gonsales, Priscila; Johnston, Samantha-Kaye; Ogu, Emmanuel C.
Professora visitante da London School of Economics e fundadora da Education Data Digital Safeguards (EDDS).